Identification of Blastocystis Subtype 1 Variants in the Home for Girls, Bangkok, Thailand - Thathaisong, Umaporn (The American Society of Tropical Medicine and Hygiene, 2013)
A cross-sectional study of Blastocystis infection was conducted to evaluate the prevalence, risk factors, and subtypes of Blastocystis at the Home for Girls, Bangkok, Thailand in November 2008. Of 370 stool samples, 118 (31.9%) were infected with Blastocystis. Genotypic characterization of Blastocystis was performed by polymerase chain reaction and sequence analysis of the partial small subunit ribosomal RNA (SSU rRNA) gene. Subtype 1 was the most predominant (94.8%), followed by subtype 6 (3.5%) and subtype 2 (1.7%). Sequence analyses revealed nucleotide polymorphisms for Blastocystis subtype 1, which were described as subtype 1/variant 1, subtype 1/variant 2. Blastocystis subtype 1/variant 1 was the most predominant infection occurring in almost every house. The results showed that subtype analysis of Blastocystis was useful for molecular epidemiological study.